2010
DOI: 10.1111/j.1464-410x.2010.09511.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prolonged operative time during robot‐assisted laparoscopic radical prostatectomy

Abstract: Study Type – Therapy (case series)
Level of Evidence 4 What’s known on the subject? and What does the study add? Robotic prostatectomy has now become the most common surgical approach in the United States for patients with prostate cancer. There is a significant learning curve for this procedure and this paper attempts to help understand what factors will make the operative times longer. Very little to date has been written on this topic. OBJECTIVE To determine risk factors for prolonged operative time (OT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
1
21
1
1
Order By: Relevance
“…A retrospective cohort study by Yong et al [14] has also attempted to identify predictors of prolonged operative time. These authors identified cumulative surgical experience, prostate weight, and nerve sparing as independent predictors of prolonged operative time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective cohort study by Yong et al [14] has also attempted to identify predictors of prolonged operative time. These authors identified cumulative surgical experience, prostate weight, and nerve sparing as independent predictors of prolonged operative time.…”
Section: Discussionmentioning
confidence: 99%
“…The primary driver of prolonged operative times during RARP is surgeon experience and this has been well described [13][14][15][16][17]. However in large volume centers, most surgeons have completed their early learning curve period; therefore, additional study of factors which increase operative time among experienced surgeons is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…[1417] Palmer and associates previously reported on the economic feasibility of RALRP. [18] In this report OR utilization was found to account for nearly 35% of the cost per procedure.…”
Section: Discussionmentioning
confidence: 99%
“…9 There is considerable variability in the length of operative time among patients and among surgeons, especially early in the surgeon's RARP experience. 8,10 Although increased operative time is known to increase the overall cost and risk of complications, 11,12 less is known about how operative time increases the risk for VTE development. In a multi-institutional series of 5951 patients undergoing laparoscopic radical prostatectomy or RARP, the incidence of symptomatic VTEs was low overall, at 0.5%, but variable among surgeons (0.2%–6.2%) and operative time was associated with increased VTE risk.…”
Section: Discussionmentioning
confidence: 99%